A six-year longitudinal study examining chronicity and timing of maltreatment effects on risk-related functional connectivity change across adolescence - Morgan Lindenmuth; Ya-Yun Chen; Tae-Ho Lee; Natalie Melville; Brooks Casas; Jungmeen Kim-Spoon (Developmental Cognitive Neuroscience)
Childhood adversity is associated with negative mental health outcomes. Research proposes sensitive periods for the effects of adversity on brain development, yet little is known about the developmental timing effects of abuse and neglect on neural mechanisms underlying risk-related decision making. This study examined 1) trajectories of neural connectivity during risk processing, and 2) how abuse and neglect during early childhood, middle childhood, and adolescence are associated with changes in functional connectivity during risk processing. A sample of 167 adolescents were assessed annually for six years (mean age 14–20 years). Adolescents completed a lottery choice task during a functional magnetic resonance imaging scan (fMRI) and reported maltreatment experiences between ages 1 and 18. Generalized psychophysiological interactions (gPPI) was used to examine task-based functional connectivity in the insula and dorsal anterior cingulate cortex (dACC) during risk processing. Growth curve models revealed increases in insula-dACC connectivity strength across adolescence. Chronic abuse statistically predicted weaker insula-dACC connectivity in late adolescence, and no significant sensitive periods emerged. Results suggest abuse may be linked to delayed maturation in salience network connectivity during risk processing and highlight the importance of distinguishing between effects of abuse and neglect on neural connectivity involved in risk-related decision making.